Analysis of the p14 and p16 mutations in cutaneous melanoma - Fątowicz, Lidia; Placek, Waldemar; Tadrowski, Tadeusz; Biernat, Wojciech (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Cutaneous melanoma is a malignant tumour derived from melanocytes that occurs primarily in the skin. It is a result of prolonged exposure to mutagenic factors and an abnormal DNA repair system. The pathogenesis of this tumour is complex and depends to a large extent on inactivation of the CDKN2A gene, whose protein products are involved in cell cycle control. The CDKN2A gene encodes two transcripts – p16 protein, which is an inhibitor of cyclin-dependent kinases (CDK4/CDK6), and p14ARF protein, responsible for stabilization of p53. Mutations in the CDKN2A gene can significantly impair the biological functions of these two proteins, and may contribute to their excessive or inadequate expression and consequently lead to malignancy. Numerous scientific studies have linked mutations in p14 and p16 in the CDKN2A gene with melanoma incidence. Objective . Analysis of p14 and p16 mutations in cutaneous melanoma in a test group of 40 tumours. Material and methods . The material consisted of paraffin-fixed biopsies with a diagnosis of melanoma confirmed histologically and immunomorphologically. In order to detect the mutation PCR-SSCP was used. Results Molecular mutations of p14 and p16 proteins in the CDKN2A gene were detected in 38 out of 40 examined tissues. This represents 95% of melanoma biopsies. Mutations were detected in all three exons of the CDKN2A gene, with the greatest frequency in the second and third exon. Conclusion . Our results indicate that mutations in p16 and p14 of the CDKN2A gene are associated with cutaneous melanoma.